Lipidomics analysis of phospholipid profiles and oxidative stability in pan-fried beef patties incorporating sacha inchi leaf extracts - Putri Widyanti Harlina; Asad Nawaz; Siti Afina Sabrina; Ernisa Adha Nur’isma; Fang Geng; Raheel Shahzad; Mohamad Rafi; Vevi Maritha; Bara Yudhistira; Ahmad Ni’matullah Al-Baarri; Heni Radiani Arifin; Edy Subroto; et al. (Scientific Reports)
Abstract High-temperature cooking methods, such as pan-frying, often accelerate lipid oxidation in meat products, negatively affecting their nutritional quality and safety; thus, natural antioxidants, such as those found in sacha inchi (Plukenetia volubilis) leaves, could be beneficial in mitigating this issue. Beef patties were additioned with sacha inchi leaf extracts at concentrations of 0.5%, 1.0%, and 1.5%, focusing on their antioxidant effects, lipid oxidation, and lipid profiles. The results showed that the addition of sacha inchi leaf extracts to pan-fried beef patties significantly reduced lipid oxidation. Higher concentrations of extracts correlated with increased antioxidant activity. Lipid profiling had distinct differences between samples, with the 1.5% of sacha inchi leaf extracts concentration showing the most promising results. Specifically, this concentration was characterized by elevated levels of LPC (Lysophosphatidylcholine)(18:2), LPE(Lysophosphatidylethanolamine)(18:2), and PA (Phosphatidic Acid)(27:2/8:0). These findings suggest that the sacha inchi leaf extracts not only mitigate lipid oxidation but also enhance the nutritional value of beef patties by influencing their lipid composition.